Perbedaan Efektivitas Variasi Konsentrasi Feri Klorida DAN Polyalumunium Chloride dalam Menurunkan Kadar Chemical Oxygen Demand (COD) pada Air Lindi TPA Jatibarang Kota Semarang - Kartika Permatasari; Onny Setiani; Mursid Raharjo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Volume of solid waste increases every year. The amount is equal with the increase of volume of leachate in landfill. The result of  earlier COD examination is 5011,34 mg/l. The number surpasses the standard which is stated in the minister of environment regulation number 5 years 2014 for water type II which is  300 mg/l. The high level of leachate COD  causes eutrophication and impairment of water use. The research aims to tell the difference between the effectiveness of PAC and Ferry Chloride  in lowering COD level of TPA Jatibarang Semarang leachate using concentration variations. The kind of research is by experimenting with pretest-posttest design .The sample is taken from leachate in landfill. The method of sample examination uses covered reflux spectrophotometrically and the analysis of data uses both Kruskall-Wallis test and Mann-Whitney test. The average of the results in examining COD is 4858,5 mg/l. The percentages of  the  decline in COD level by using PAC concentration variations which are 4%, 8%, and 12% successively are 3.9%, 6.9% and 6.7%. Meanwhile, by adding Ferry Chloride with the same concentrations, successively decrease the COD levels into 9.21%, 36.62%, and 36.74%. The result of Kruskall-Wallis test shows that there are differences in the decline percentages of COD level after treatment using PAC and Ferry Chloride (p-value 0.040 and 0.041). The result of Mann-Whitney test shows that the differences in the decrease of COD level of leachate is significant (p-value=0.05). However, the concentration of 12% Ferry Chloride is the concentration that lowers the greatest COD level,although it hasn’t reached the quality standard yet.